ChemInform Abstract: Continuous‐Flow Technology — A Tool for the Safe Manufacturing of Active Pharmaceutical Ingredients. Issue 30 (July 2015) - Gutmann, Bernhard; Cantillo, David; Kappe, C. Oliver
Abstract Review: [202 refs.